Bacillus licheniformis Bacillus licheniformis trehalose‐6‐phosphate hydrolase structures suggest keys to substrate specificity. Issue 1 (1st January 2016) - Lin, Min-Guan; Chi, Meng-Chun; Naveen, Vankadari; Li, Yi-Ching; Lin, Long-Liu; Hsiao, Chwan-Deng
Abstract : Wild‐type and mutant structures of B. licheniformis B. licheniformis trehalose‐6‐phosphate hydrolase suggest new insight into the characteristics and substrate specificity of trehalose‐6‐phosphate hydrolase. Abstract : Trehalose‐6‐phosphate hydrolase (TreA) belongs to glycoside hydrolase family 13 (GH13) and catalyzes the hydrolysis of trehalose 6‐phosphate (T6P) to yield glucose and glucose 6‐phosphate. The products of this reaction can be further metabolized by the energy‐generating glycolytic pathway. Here, crystal structures of Bacillus licheniformis Bacillus licheniformis TreA ( Bl Bl TreA) and its R201Q mutant complexed with p p ‐nitrophenyl‐α‐d d ‐glucopyranoside (R201Q– p p PNG) are presented at 2.0 and 2.05 Å resolution, respectively. The overall structure of Bl Bl TreA is similar to those of other GH13 family enzymes. However, detailed structural comparisons revealed that the catalytic site of Bl Bl TreA contains a long loop that adopts a different conformation from those of other GH13 family members. Unlike the homologous regions of Bacillus cereus Bacillus cereus oligo‐1, 6‐glucosidase ( Bc Bc Ogl) and Erwinia rhapontici Erwinia rhapontici isomaltulose synthase (NX‐5), the surface potential of the Bl Bl TreA active site exhibits a largely positive charge contributed by the four basic residues His281, His282, Lys284 and Lys292. Mutation of these residues resulted in significant decreases in the enzymatic activity of Bl Bl TreA. Strikingly, the 281 281 HHLK 284 284 motif and Lys292 play critical roles in substrate discrimination by Bl Bl TreA.